Application of Polyaniline Modified Graphite Electrodes for Capacitive Deionization of Aqueous NaCl Solutions - Li, Qiuhong (Asian Journal of Chemistry, 2010)
Polyaniline/graphite composite electrodes were used as the electrodes of capacitive deionization apparatus and the electrodeposition conditions of polyaniline film were studied in order to optimize the capacitive deionization unit. The results showed that the potential -0.85 V for potentiostatic method or current 0.5 A for galvanostatic method was suitable for the electrodeposition of polyaniline film by the measurement of the conductivity of aqueous NaCl solution. Meanwhile, the capacitive deionization unit could be regenerated easily.